The acute effects of a warm-up including static or dynamic stretching on countermovement jump height, reaction time, and flexibility - Perrier, E. T.; Pavol, M. J.; Hoffmann, M. A. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this research was to compare the effects of a warm-up with static vs. dynamic stretching on countermovement jump (CMJ) height, reaction time, and low-back and hamstring flexibility and to determine whether any observed performance deficits would persist throughout a series of CMJs. Twenty-one recreationally active men (24.4 ± 4.5 years) completed 3 data collection sessions. Each session included a 5-minute treadmill jog followed by 1 of the stretch treatments: no stretching (NS), static stretching (SS), or dynamic stretching (DS). After the jog and stretch treatment, the participant performed a sit-and-reach test. Next, the participant completed a series of 10 maximal-effort CMJs, during which he was asked to jump as quickly as possible after seeing a visual stimulus (light). The CMJ height and reaction time were determined from measured ground reaction forces. A treatment × jump repeated-measures analysis of variance for CMJ height revealed a significant main effect of treatment (p = 0.004). The CMJ height was greater for DS (43.0 cm) than for NS (41.4 cm) and SS (41.9 cm) and was not less for SS than for NS. Analysis also revealed a significant main effect of jump (p = 0.005) on CMJ height: Jump height decreased from the early to the late jumps. The analysis of reaction time showed no significant effect of treatment. Treatment had a main effect (p < 0.001) on flexibility, however. Flexibility was greater after both SS and DS compared to after NS, with no difference in flexibility between SS and DS. Athletes in sports requiring lower-extremity power should use DS techniques in warm-up to enhance flexibility while improving performance.